Pelanggaran Hak Cipta dalam Konten Video YouTube: Perspektif Fikih Jinayah - Basir, Firmansyah; Syatar, Abdul (Universitas Islam Negeri Alauddin Makassar, 2023)
Copyright accompanies any content uploaded to the youtube channel. Content that has been uploaded is sometimes re-uploaded by editing and changing without including the source. The main problem in this study is how copyright infringement in Youtube video content is viewed from the perspective of Islamic Law. The purpose of this study is to determine copyright infringement in Youtube video content from the perspective of Islamic Law. This research uses a type of library research using a qualitative descriptive approach. The data sources used are primary data in the form of books, journals, videos, and so on including secondary data. The results showed that actions that can be indicated as copyright infringement of youtube video content are the use, taking, duplication and/or alteration of a substantial whole or part by not mentioning the source and name of the video content owner, taking advantage (commercial purposes) and causing losses to the owner of the youtube video content. Meanwhile, according to the perspective of Islamic law, it is clearly stipulated in the MUI Fatwa Decision No. 1/MUNAS/MUI/5/2005 concerning the Protection of Intellectual Property Rights (IPR) and MUI Fatwa No. 1/2003 that all use, disclosure, manufacture, use, sale, import, export, distribution, delivery, provision, announcement, reproduction, plagiarism, forgery and/or piracy of someone else's youtube video content is a form of tyranny and the law is haram according to Islamic law.